Design of a chromogenic substrate for elastase based on split GFP system proof of concept for colour switch sensors - Ferreira, Ana V. (2019)
Recent studies have demonstrated that human neutrophil elastase (HNE) can be used as marker for inflammation/infection of chronic wounds since it was found to be present in high concentration in exudate collected from chronic wounds. Biosensors used in wound care benefit from a chromogenic signalling due to the readiness of signal interpretation, but the most common use faint yellow chromogenic molecules such as p-nitroaniline (pNa). In addition, if to be converted into smart dressings, the colour of the detection system should not be masked by the exudates colour. In this work, we designed a chromogenic substrate for HNE aiming to be incorporated in a smart dressing as a colour switch sensor. The substrate was developed using the GFP-like chromoprotein ultramarine (UM), following the split GFP technology. The cleavage sequence for HNE (Ala-Ala-Pro-Val) was embedded into the sensing moiety of the substrate corresponding to the 11th -sheet. In the presence of HNE, the 11th -sheet is able to interact to the signalling moiety composed of the 1-10 incomplete barrel, allowing the re-establishment of the chromophore environment and, hence, the colour production. Structural homology and molecular dynamics simulations were conducted to aid on the disclosure of the structural changes that are the base of the mechanism of action of this HNE switch substrate. Our findings explore the possible application of GFP-like chromogenic sensors in point-of-care devices for the evaluation of the wounds status, representing a major step in the medical field.